Anesthesia Management and Postanesthetic Recovery Following Endoscopic Sinus Surgery. (11th July 2020) - Laporta, Mariana L.; O'Brien, Erin K.; Stokken, Janalee K.; Choby, Garret; Sprung, Juraj; Weingarten, Toby N.
Abstract : Objectives: Delayed anesthesia recovery following endoscopic sinus surgery (ESS) can be an indicator of immediate complications and negatively impact healthcare efficiency. This study aims to examine clinical factors with a focus on improving clinical practice. Methods: Medical records of patients undergoing ESS under general anesthesia from 2014 to 2018 were reviewed. Based on the interquartile range of anesthesia recovery for the cohort, patients in the upper quartile were categorized as "prolonged" and the lowest three quartiles as "goal" recovery. Patient and surgical characteristics were investigated. Results: Analyzing 416 patients who underwent ESS, the median anesthesia recovery time was 48 [35–66] minutes. Prolonged recovery was associated with higher body mass index (odds ratio 1.50 [95% confidence interval 1.03–2.18] per 10 kg/m 2, P = .03) and surgical duration (1.37 [1.10–1.72] per hour, P < .01). Inversely, goal recovery was associated with preoperative acetaminophen (0.61 [0.38–0.98], P = .04) and intraoperative remifentanil (0.55 [0.32–0.93], P = .03). Patients with prolonged recovery had higher rates of severe pain (33 (31.7%) vs. 25 (8.0%), P < .01), respiratory depression (7 [6.7] vs. 2 [0.6], P < .01), oversedation (39 [37.5] vs. 39 [12.5], P < .01), and the need for rescue opioids (52 [50] vs. 71 [22.8], P < .01). In addition to reduced postanesthesia recovery time, patients who were administered preemptive acetaminophen had lower rates of severe pain (OR 0.55 [0.31–0.98], P = .04) and nausea and vomiting (0.39 [0.17–0.87], P = .02). Conclusion: Our findings substantiate the use of acetaminophen and remifentanil in ESS, facilitating anesthesia recovery. Broadly consideration of preemptive acetaminophen could further increase postoperative comfort in ESS. Level of Evidence: 4 – Retrospective. Laryngoscope, 131:E815–E820, 2021